Knowledge and using of unpharmacological methods of labor pain softening in opinion of pregnant women in Crakow hospitals - Śledzińska, Urszula; Leja-Szpak, Anna; Barłowska-Trybulec, Marta; Prażmowska, Barbara; Jaworek, Jolanta (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introduction. Pain is an inseparable element of labor. Its excessive feeling elicits a number of negative reactions affected on mother and child. Therefrom exist the necessity to elaborate the activities aimed to decrease of this feeling to the acceptable level of women in labor. There is a potential in natural methods of labor pain softening. Aim. Performance of knowledge and application of natural methods of labor pain softening and the assessment of this methods efficacy. Material and methods. The study group consisted of 105 women in labor, after natural birth. The method of diagnostic survey and original questionnaire were applied in the study. All data were analyzed using Statistica version 5.0 (p = 0,05). Results. Knowledge about methods of labor pain softening does not depend on age, number of births or place of residence but increases proportionally with the level of education. Pregnant women makes use of unprofessional sources such as members of family, friends and from media. Medical staff as an information source provides determined minority. Delivered women using slight part of natural methods of pain softening such us: water immersion, movement and vertical poses, aware breathing and the assistance of loved one. Conclusions. The potential of natural methods of labor pain softening isn’t fully exploited by the women in labor. It could resulted from the lack of clear arguments which affirm the efficacy of this methods and using unprofessional sources about this theme by pregnant women.